Pengaruh Kinerja Karyawan Terhadap Kesuksesan Perusahaan - Wahyu Risyah, Dhimas; Syahidan Ilmi; Ilham; Helfira Citra (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2024)
Employee performance is an important element in a company. Good employee performance can make the company achieve its goals. Therefore, companies must understand the factors that influence employee performance and how to improve it. This research aims to examine the influence of employee performance on company success and find out how to increase employee performance strategies in achieving company goals. This research uses quantitative research methods with data collection techniques through questionnaires. The sample for this research is company employees who were randomly selected. The research results show that employee performance has a significant influence on the company's success. Factors that influence employee performance are motivation, leadership, and work environment. High employee motivation can improve employee performance, while effective leadership can increase employee motivation. A comfortable and enjoyable work environment can also improve employee performance. This research also found that an effective strategy for improving employee performance is to provide incentives and rewards, provide training and development, and create a comfortable and enjoyable work environment.